2015
DOI: 10.1001/jamaneurol.2014.4769
|View full text |Cite|
|
Sign up to set email alerts
|

Mutation inCPT1CAssociated With Pure Autosomal Dominant Spastic Paraplegia

Abstract: The family of genes implicated in hereditary spastic paraplegias (HSPs) is quickly expanding, mostly owing to the widespread availability of next-generation DNA sequencing methods. Nevertheless, a genetic diagnosis remains unavailable for many patients.OBJECTIVE To identify the genetic cause for a novel form of pure autosomal dominant HSP. DESIGN, SETTING, AND PARTICIPANTS We examined and followed up with a family presenting to a tertiary referral center for evaluation of HSP for a decade until August 2014. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 37 publications
4
57
1
Order By: Relevance
“…A recent study by Rinaldi et al [90] This study also confirmed the expression of CPT1C in soma and dendritic and axonal projections of motor neurons, as well as its localization to the ER and not to mitochondria. A relevant finding from this study was the interaction between CPT1C…”
Section: Accepted M Manuscriptsupporting
confidence: 79%
See 4 more Smart Citations
“…A recent study by Rinaldi et al [90] This study also confirmed the expression of CPT1C in soma and dendritic and axonal projections of motor neurons, as well as its localization to the ER and not to mitochondria. A relevant finding from this study was the interaction between CPT1C…”
Section: Accepted M Manuscriptsupporting
confidence: 79%
“…The findings that ceramide and sphingosine levels were reduced in brain motor regions of CPT1C KO mice [47] led the authors to propose this alteration as a potential cause of motor impairment in these animals. These deficits in CPT1C KO mice are consistent with the symptoms associated with human CPT1C mutation recently observed in hereditary spastic paraplegia, a human disorder affecting motor function [90].…”
supporting
confidence: 88%
See 3 more Smart Citations